A retrospective observational study of critically unwell patients retrieved from Thames Hospital between April 2018 and December 2020 - Meg Topping; Lisa TenEyck; Samuel Bell; Rory Miller (CSIRO Publishing, 2021)
ABSTRACT INTRODUCTIONIn New Zealand, critically ill patients who present to rural hospitals are typically treated, stabilised and transferred to facilities where more appropriate resources are available. AIMThe aim of this study was to describe patients who presented critically unwell and required retrieval from Thames Hospital in the Waikato region. METHODSNotes were reviewed retrospectively for patients who were retrieved from Thames Hospital between 1 April 2018 and 31 December 2020. Patients were excluded if they were retrieved from the offsite birthing centre or their notes were not available to the authors. RESULTSDuring the study period, 56 patients were retrieved by intensive care teams based at Waikato, Starship or Auckland Hospitals. Patients had a median age of 57 years and most were female (60.7%). Māori patients were over-represented in the retrieval cohort compared with the population presenting to the emergency department (30.4% vs. 20.1%, P<0.001). We found that 41% of patients presented after-hours when there was only one senior medical officer available on site and 70 procedures were performed, including rapid sequence induction, which was required by 19.6% of patients. DISCUSSIONThis study describes a population of critically unwell patients who were retrieved from a rural hospital. The key finding is that nearly half of these patients presented after-hours when there was only one senior medical officer available on site. This doctor also has sole responsibility for all other patients in the hospital. We recommend that referral centres streamline the retrieval processes for rural hospitals.